Developing flexibility in thinking among kindergarten children at the U.P. Elementary School - Fonacier, Nieves Z. 1925- (College of Education, University of the Philippines Diliman, 1975)
The purpose of the study is to suggest instructional activities designed to develop spontaneous and adaptive flexibility in the thinking of Kindergartners. Specifically, the activities were delineated into two categories as suggested by Guilford: spontaneous flexibility skills and adaptive flexibility skills. The study was approached through integrative research. Literature on creative teaching and productive solving skills form the major theoretical framework. The work of the children in these activities have been included to show their flexibility in thinking skills. However, no attempt has been done to present statistically their flexibility scores due to the fact that no factorial tests have been designed.